Pengaruh Pencatatan Keuangan, Modal Usaha, Biaya Operasional, Pengelolaan Aset, dan Penggunaan Teknologi terhadap Tingkat Pendapatan Nelayan: Studi Kasus pada Nelayan Tradisional di Keruak Lombok Timur - Dina Amalya Putri; Herawati Khotmi (Journal of Innovative and Creativity, 2025)
This study aims to examine the influence of financial recording, business capital, operational costs, asset management, and technology use on the income levels of traditional fishermen in Keruak . The study was conducted using a quantitative approach and analytical techniques using Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS software. A sample of 86 traditional fishermen was obtained using a purposive sampling method. The analysis results indicate that financial recording, operational costs, and asset management significantly influence fishermen's income. Meanwhile, business capital and technology use did not show a significant effect. The implications of these findings point to the importance of financial management and operational efficiency in improving the welfare of traditional fishermen.